Hubungan Dukungan Keluarga dengan Kepatuhan Diet Pada Lansia Penderita Hipertensi di Puskesmas Bareng Kota Malang - Talita Beta Oktavia; Oda Debora; Febrina Secsaria Handini (Malahayati Nursing Journal, 2025)
ABSTRACT Hypertension is a serious health problem, systolic and diastolic blood pressure increases above normal limits. One of the efforts to lower high blood pressure is the hypertension diet. In overcoming the elderly who suffer from hypertension, this family support can help the elderly in overcoming problems and carrying out hypertension diet adherence correctly. This study was used to determine the relationship between family support and dietary adherence in the elderly with hypertension at the Bareng Health Center in Malang City. This type of research is quantitative correlation using the cross-sectional method, with a population of 136 respondents and a sample of 102 respondents who have been selected using the purposive sampling technique. The instruments used were general data, family support and dietary adherence. Data analysis uses the spearman correlation test. The research was conducted at the Bareng Health Center in Malang City. The results of the statistical test showed (p-value 0.0070.05) this means that there is a relationship between family support and hypertensive diet adherence in the elderly at the Bareng Health Center in Malang City. Based on the results of the study, it was concluded that family support affects hypertensive dietary adherence in the elderly. The family plays an important role in accompanying the elderly to help overcome hypertensive dietary adherence. The better the family support provided, the more it increases the compliance of the elderly in carrying out the diet. It is hoped that the elderly with hypertension can adhere to the hypertension diet well such as eating foods that are low in salt, low in cholesterol, high in fiber and low in calories to minimize complications due to hypertension. Keywords: Hypertension, Family Support, Compliance, Hypertension Diet  ABSTRAK Hipertensi menjadi permasalahan kesehatan yang serius, tekanan darah sistolik dan diastolic meningkat diatas batas normal. Salah satu upaya menurunkan tekanan darah tinggi yaitu diet hipertensi. Dalam mengatasi lansia yang menderita penyakit hipertensi dukungan keluarga ini dapat membantu lansia dalam mengatasi masalah dan menjalankan kepatuhan diet hipertensi dengan benar. Penelitian ini digunakan untuk mengetahui hubungan dukungan keluarga dengan kepatuhan diet pada lansia penderita hipertensi di Puskesmas Bareng Kota Malang. Jenis penelitian ini yaitu kuantitatif korelasional menggunakan metode cross-sectional, dengan populasi 136 responden dan sampel sejumlah 102 responden yang sudah dipilih menggunakan teknik purposive sampling. Instrumen yang digunakan data umum, dukungan keluarga dan kepatuhan diet. Analisa data menggunakan uji korelasi spearman. Penelitian dilakukan di puskesmas Bareng Kota Malang. Berdasarkan hasil penelitian disimpulkan bahwa dukungan keluarga mempengaruhi kepatuhan diet hipertensi pada lansia. Keluarga berperan penting dalam mendampingi lansia untuk membantu mengatasi kepatuhan diet hipertensi. Semakin baik dukungan keluarga yang diberikan maka semakin meningkatkan kepatuhan lansia dalam menjalankan diet. Diharapkan lansia penderita hipertensi dapat mematuhi diet hipertensi dengan baik seperti makan makanan yang rendah garam, rendah kolesterol, tinggi serat dan rendah kalori agar meminimalkan terjadinya komplikasi akibat hipertensi. Kata Kunci: Hipertensi, Dukungan Keluarga, Kepatuhan, Diet Hipertensi